Towards Systems Thinking in Ethical Management to the Environment: A Solution for Conflict of Interest - Putri Larasati, Ika (Jurnal Ekonomi Modernisasi, 2010)
Multiple stakeholders refer to different interests that are vulnerable to create conflict of interest. The condition requires an effective management to satisfy stakeholders without ignoring ethical practices to the environment. It demands systems thinking which makes companies realise that their activities influence stakeholders whilst stakeholders’ actions have impact on companies. However, several companies preclude the systems thinking which gives consequence to unsolved conflict and even creates worse problems. Gunns Limited Company Australia (Gunns) is one of example ofthese companies.Gunnsactivities in the Tasmania forest generated public criticisms because Gunns was considered as a firm that deterioratedthe environment, humans’health and communities’ job. Different stakeholders’ views on this case might lead to environmental safety or environmental destructions. With this background, this essay attempts to analyzethe application of systems thinking (under stakeholder theory) in the process of ethical management to the environment in order to solve the conflict of interests. Hopefully, this paper will significantly contribute to overcome similar issues in Indonesia and also contributes to further researches related to systems thinking as a solution for conflict of interest.